Clinical efficacy of soft tissue micro-adjustment combined with traction in pediatric atlantoaxial subluxation: a randomised controlled study protocol using musculoskeletal ultrasound technology - Yin, Shuaizi; Luo, Huasong; Guo, Yinfeng; Cai, Ge; Wu, Ting; Ying, Shuaiyu; Zhang, Xiao; Sun, Yi; Zeng, Xiayang (Frontiers in Pediatrics, 2025)
BackgroundAtlanto-axial rotatory subluxation (AARS) in pediatric patients is characterized by abnormal or restricted motion between the atlas and axis vertebrae, typically presenting with neck pain, limited mobility, torticollis, and muscle stiffness. Cervical atlanto-occipital joint x-ray in open-mouth position or CT scan reveals an atlanto-occipital distance (AOD) of 2 mm < AOD < 5 mm, or a bilateral atlanto-occipital lateral distance (B-LAD) ≥ 2 mm. Although traditional manipulative and bone-setting techniques in Traditional Chinese Medicine have demonstrated clinical benefits, robust empirical evidence remains limited. Musculoskeletal ultrasound (MUSU), as a modern diagnostic modality, has gained popularity for assessing musculoskeletal disorders.MethodsThis study utilized a randomized controlled trial design, where eligible patients diagnosed with AARS were, randomly assigned (1:1) to either a treatment group (gentle manipulative technique combined with continuous traction) or a control group (traction plus cervical collar immobilization). The treatment group received treatment twice daily, five days per week, for two weeks. The control group received the same traction protocol but wore a neck brace immediately after each traction treatment. The primary outcome measure was musculoskeletal ultrasound (MUSU) findings, while secondary outcomes include Visual Analogue Scale (VAS) pain scores and Neck Disability Index (NDI) scores. Both groups were assessed at baseline, post-treatment, two weeks, and six months after treatment.DiscussionThe primary objective of this study aims to quantitatively assess the efficacy and safety of gentle manipulative therapy combined with continuous traction in pediatric AARS, using MUSU technology.Clinical Trial Registration: http://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025001572.